Analysis of photovoltaic module degradation: An experimental investigation on the correlation between partial shading, hot spots, and EVA discoloration - Islam, Md. Imamul; Mohd Shawal, Jadin; Al Mansur, Ahmed; Mohd Salmizan, Mohd Zain; Ul Haq, Mohammad Asif (Springer, 2024)
The performance of solar PV modules is impacted by several environmental stressors, including high ambient temperatures, inadequate sunlight, shade, dust, soiling, cell damage, etc. To guarantee long-term clean and sustainable energy generation, it is crucial to understand performance degradation and PV module reliability. In this current research, an experimental investigation on the degradation analysis of three 80 W monocrystalline PV modules that have been exposed for approximately ten years in a tropical environment in Malaysia as well as a correlation between partial shading, hot spots, and EVA discoloration has been conducted. The use of visual inspection, I–V curve measurement, thermal imaging, and degradation estimation have all been used to conduct an extensive study throughout this work. The outcome demonstrates each module’s rate of degradation and hot spot phenomena because of the partial shading impact. Hot spots development is to blame for the EVA discoloration seen on Panel 2 and Panel 1 cells. The degradation rates of Panel 1, Panel 2, and Panel 3 are 0.496%, 1.264%, and 0.189% per year, respectively. The study addressed that dust and dried algae serve as mechanisms of PV degradation, and hot spots caused by partial shade may impact cell discoloration.